2007
DOI: 10.1071/ar06391
|View full text |Cite
|
Sign up to set email alerts
|

Yield-limiting potential of Beet western yellows virus in Brassica napus

Abstract: Losses in seed yield and quality caused by infection with Beet western yellows virus (BWYV) alone or in combination with direct feeding damage by Myzus persicae (green peach aphid) were quantified in field experiments with Brassica napus (canola, oilseed rape) in the ‘grainbelt’ region of south-western Australia. Plants infected with BWYV and infested with M. persicae were introduced into plots early to provide infection sources and spread BWYV to B. napus plants. Insecticides were applied as seed dressings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…Symptoms of TuYV infection are often reminiscent of abiotic stress, particularly nutrient deficiency, and can include reddening of leaves and stunted growth. In addition, TuYV infection has been shown to reduce seed yield in single OSR plants by 40-50% (Schroeder 1994) and cause yield losses in OSR crops of 11-46% (Graichen and Schliephake 1999;Jay et al 1999;Jones et al 2007). In the past, the most common strategy to control TuYV has been the use of chemical measures against the vector, in particular insecticide (neonicotinoid)-treated seeds, but most of these treatments are now banned for OSR in the EU, emphasising the need for alternative control measures such as natural plant resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of TuYV infection are often reminiscent of abiotic stress, particularly nutrient deficiency, and can include reddening of leaves and stunted growth. In addition, TuYV infection has been shown to reduce seed yield in single OSR plants by 40-50% (Schroeder 1994) and cause yield losses in OSR crops of 11-46% (Graichen and Schliephake 1999;Jay et al 1999;Jones et al 2007). In the past, the most common strategy to control TuYV has been the use of chemical measures against the vector, in particular insecticide (neonicotinoid)-treated seeds, but most of these treatments are now banned for OSR in the EU, emphasising the need for alternative control measures such as natural plant resistance.…”
Section: Introductionmentioning
confidence: 99%
“…BWYV transmitted by M. persicae caused a significant reduction on yield which averaged 34%. This result was based on three studies from WA, namely Jones and Hawkes (2002) and Jones et al (2003Jones et al ( , 2007, who found similar yield reductions in the range 30-39%, respectively (data extracted from publications), based on artificial aphid inoculations. Artificial inoculations used in virus trials may lead to a high and early incidence of disease (particularly as plants were inoculated at (Berlandier 2004).…”
Section: Canolamentioning
confidence: 83%
“…Virus data from field assays were derived from artificial inoculations, whereas feeding data were derived from natural infestations, except in one study where a naturally infested crop was supplemented with aphids (Berlandier 2004). Canola yield tended to be affected more by virus injury than feeding injury; overall virus injury caused an average yield reduction of 34% (SD = 23) (Jones & Hawkes 2002;Jones et al 2003Jones et al , 2007 while feeding injury caused an average reduction of 23% (SD = 14) (Berlandier 2004;Jenkins et al 2011). All Australian data collated came from studies conducted in WA and NSW, despite canola being an important crop in VIC and SA with production averaging 331 000 and 260 000 tonnes, respectively, for 2009-2010 (sourced from Australian Bureau of Statistics (ABS)).…”
Section: Canolamentioning
confidence: 99%
“…Imidacloprid has been shown to reduce incidence of persistently transmitted, aphid‐borne viruses, the transmission of which has been associated with phloem feeding (waveform E in EPG recordings) . For example, a reduction in feeding time and percentage of individuals that reached the phloem is believed to be responsible for reduced transmission of Barley yellow dwarf virus, a phloem‐borne virus, by Schizaphis graminum (Rondani) .…”
Section: Resultsmentioning
confidence: 99%